The Analysis of Masculinity in Advertising: A Qualitative Study Based on Consumer Perceptions - Kreicbergs Toms (Economics and Business)
The aim of the research was to explore Generations Z’s perceptions of masculinity in advertising and determine which type of masculinity and which masculinity characteristics consumers favor in a masculine character or the advertising message centered around masculinity. The author conducted three focus groups with a demographic: Latvian Generation Z. Qualitative content analysis of the focus group interview transcripts was conducted using Nvivo 11 qualitative data analysis software. The research concluded that Latvia’s Generation Z preferred modern masculinity depictions in advertising over traditional ones, and advertisers should not depict masculinity with stereotypes but rather emphasize diversity, self-acceptance, and emotionality and depict masculinity as an important topic.